Selected structural information on spatial planning studies at German universities - Schöfer, Markus (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The Bologna Process aims to create an European Higher Education Area by 2010. At the moment, study courses in the field of spatial planning are also getting reorganized. This article describes consecutive bachelor and master study courses in spatial planning by means of a variety of attributes, for example the maximal number of credit points and the duration of the study course. The following universities are included in the synoptical comparison: Berlin, Cottbus, Dortmund, Hamburg-Harburg, Kaiserslautern, Kassel und Nürtingen-Geislingen.